Politeness Strategies in Cross-Cultural Academic Communication between Mandailing Natal Students and Culturally Diverse Lecturers - Yahsya, Akhrif; Santoso, Didik; Antonio, Joemar; Suadi, Suadi (STAIN Majene, 2026)
Although politeness in academic communication has been widely discussed in pragmatic studies, limited research has examined how students from local cultural backgrounds employ politeness strategies when interacting with lecturers from different cultural backgrounds in Indonesian higher education settings. This gap is important to address because differences in cultural norms and communication styles may lead to misunderstandings and affect the effectiveness of lecturer–student interaction. This study aims to investigate the politeness strategies used by Mandailing Natal students when interacting with lecturers from different cultural backgrounds at STAIN Mandailing Natal. This study employed a qualitative pragmatic research design with a sociopragmatic approach. The participants consisted of 15 Mandailing Natal students and 6 lecturers from non-Mandailing cultural backgrounds. The data were collected through classroom observations, audio-recorded lecturer–student interactions, academic consultation recordings, semi-structured interviews, and field notes. The data were analyzed using pragmatic discourse analysis based on Brown and Levinson’s politeness theory. The findings reveal that students predominantly employed negative politeness strategies, including indirect expressions, hedging, apologetic forms, and softened statements to show respect and minimize imposition toward lecturers. Students frequently avoided direct disagreement and tended to communicate cautiously due to cultural values emphasizing respect for authority and social harmony. In contrast, lecturers generally used more direct communication styles when giving feedback, instructions, and asking questions. These differences in communication styles sometimes created misunderstandings during classroom discussions and thesis supervision sessions. Students often hesitated to ask for clarification, while lecturers sometimes interpreted students’ silence as passiveness or lack of preparation. The study concludes that politeness strategies in lecturer–student interaction are strongly influenced by cultural values, social hierarchy, and academic roles. The findings highlight the importance of pragmatic and intercultural awareness in higher education communication in order to reduce misunderstandings and support more effective academic interaction.